Geochronology, pyrite trace elements, and sulfur isotope geochemical characteristics of the Saibagou gold deposit in the eastern part of the northern Qaidam Basin - Xing, Jia; Wang, Jianguo; Liu, Jianbao; Liu, Yanguang; Bian, Kai; Liu, Jianwei; Cai, Lina; Wei, Shengyun (Frontiers in Earth Science, 2023)
The Saibagou gold deposit, located in the eastern part of the tectonic belt of the northern Qaidam Basin in western China, has its gold ore bodies strictly controlled by the regional fault system. Despite this understanding, there remain controversies surrounding the deposit’s metallogenic epochs, sources of ore-forming materials, and properties of ore-forming fluids. To address these controversy, the metallogenic process of the Saibagou gold deposit can be further determined by analyzing the U-Pb ages of hydrothermal zircons in the gold-bearing quartz veins and investigating the trace element and sulfur isotope compositions of pyrite in the gold deposit. This study does not focus on the mineral characteristics susceptible to interference by the metallogenic condition in gold ore bodies. Instead, it offers a detailed discussion on stable associated minerals and their indicative markers formed in the process of gold mineralization. The results of this study showed that the metallogenic process of the gold deposit can be categorized into the following stages: 1) quartz – pyrite veins, 2) milky-white quartz - pyrite - native gold veins, 3) hoary quartz - native gold - polymetallic sulfide veins. As indicated by the U-Pb ages of hydrothermal zircons in the gold-bearing quartz veins, the Saibagou gold deposit has two metallogenic ages, namely 423.91±4.5 Ma (the Silurian) and 470.18±4.92 Ma (the Ordovician). The Silurian metallogenic age, predominates and nearly aligns with the expansion of the regional NWW-trending brittle-ductile shear zone, followed by the Ordovician metallogenic age. Data on the trace elements and sulfur isotopes of pyrite, show that the Saibagou gold deposit has similar pyrite compositions in the three metallogenic stages. Gold in the deposit primarily occurs as native gold or minor petzite inclusions and has a very low lattice gold concentration. As indicated by the concentrations of elements such as Co, Ni, and As in the pyrite, as well as the variation range of δ34S values, the ore-forming fluids were derived from low-temperature arsenic-bearing acidic magmas. In addition, the primary ore-forming materials appear to encompass mantle-derived materials from the deep Earth.